CHRONIC BACTERIAL RHINITIS IN A DOMESTIC CAT - Luh Putu Syamadina Pramesya Nareswari; Arjentinia, I Putu Gede Yudhi; Suartha, I Nyoman (Buletin Veteriner Udayana, 2024)
Rhinitis is one of the most common respiratory diseases in cats. Rhinitis is an inflammation of the nasal mucosa characterized by sneezing, serous to hemorrhagic discharge, and stridor breathing sounds. The purpose of writing this article is to obtain the definitive diagnose and the treatment from anamnesis, clinical symptoms, physical examination, and laboratory examination that were carried out to animal case. The animal case is a 2-year-old male domestic cat weighing 3.29 kg. The owner convey that her pet had been sneezing for 1 month containing yellowish-white discharge, lost voice, and rough breathing. A physical examination was carried out and it was found that the cat had a habit of sneezing, mucopurulent discharge from the nose, dried discharge from the nose, the cat often opened its mouth, stridor breathing sounds, and often meowed hoarsely or even without a sound. The examination was continued with a hematology examination with lymphocytosis results indicating inflammation. Cytology showed neutrophil infiltration in the cat's nasal discharge. Radiographic examination showed a mild bronchial pattern in the lungs. Culture of nasal discharge was positive for Staphylococcus spp. The cat was diagnosed with rhinitis and was treated with the antibiotic Doxycycline hyclate twice daily orally, anti-inflammatory Methylprednisolone once daily orally, mucolytic Bromhexine hcl once daily, and multivitamins once daily. On the 10th day after treatment, the cat was no longer sneezing, had no nasal discharge, and the cat's voice had returned to normal.